A Teaching Tool to Visually Illustrate How Manipulating the Physiology of the Ventilatory Muscle Pump Alters Functional Performance. Issue 1 (March 2015) - Sobush, Dennis C.
Abstract : This clinical perspective article describes an inexpensive pedagogical tool intended for use in a laboratory setting as part of a cardiovascular and pulmonary physical therapy course. It uses a dual balance scale schematic/model. As a teaching resource, physical therapy students can use it to visually reinforce their understanding of the complex cause-and-effect interplay between physiological factors that affect ventilatory muscle pump (VMP) performance for sustained breathing or contribute to VMP fatigue/failure.